Development of an Intelligent Waste Identification System Based on the YOLOv11 Algorithm - Sheryl Nicole Gunawan; Usman Sudibyo (Politeknik Negeri Batam, 2026)
Effective waste management is a critical challenge in urban environments, necessitating the development of automated systems for efficient waste classification. This study aims to develop an intelligent system for detecting and classifying waste into organic and inorganic categories using the You Only Look Once (YOLO)v11 object detection algorithm. The proposed system identifies the presence and location of waste objects through bounding boxes and classifies them based on their visual characteristics to facilitate real-time detection. Experimental results demonstrate the model's effectiveness, achieving an overall accuracy of 0.717. Performance analysis indicates consistent reliability, with